Exploring"Whistle Blower’s" Intentions: Exploration Study On University Students - Dodi Wirawan I (Jurnal Manajemen, 2018)
Recently the epidemic corruption case in Indonesia has become increasingly rampant. Efforts to eradicate corruption which has been committed after the reformation era in 1998 do not equal with the corruption proliferation in the decentralization era. In the last five years many corruption cases have been revealed due to the role of whistle blower. This study aimed to explicate the main intentions of whistle blowers who uncover corruption cases. The perception study were conducted on Brawijaya University students so that understanding the intentions of these whistle blowers can be found in the government sector which in fact is a focus of corruption practices. A factor analysis and statistical descriptive analysis were conducted to answer the main question of this study which revealed that there are three main factors in whistle blowing intention and that demographic variables do not affect the perception of whistle blowing intention.